Analisis Rasio Keuangan untuk Menilai Kinerja Perusahaan - Joni Hendra; Andika M Iqbal; M Pillo Alfarabi; Rosa Dina; Tria Oca Ariska (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to analyze the financial ratios to evaluate company performance. The research background highlights the importance of financial health for sustainable business operations. This study employs a quantitative descriptive method, utilizing financial statements for data collection. The findings indicate that certain financial ratios are strong indicators of a company's financial stability and operational efficiency, providing valuable insights for stakeholders.